2016
DOI: 10.1177/0004563216671009
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of serum 3-epi-25-hydroxyvitamin D3, 25-hydroxyvitamin D3 and 25-hydroxyvitamin D2 in infant, paediatric and adolescent populations of Korea using ultra-performance liquid chromatography-tandem mass spectrometry

Abstract: Background We evaluated the performance of ultra-performance liquid chromatography-tandem mass spectrometry to measure serum 3-epi-25-hydroxyvitamin D, 25-hydroxyvitamin D and 25-hydroxyvitamin D concentrations in 519 infant, paediatric and adolescent serum samples in Korea. Methods We used a Kinetex XB-C18 column and isocratic methanol/water (77.5/22.5, v/v) with 0.025% (v/v) high-performance liquid chromatography solvent additive flowing at 0.25 mL/min, yielding an 11 min/sample run time. A TQD triple quadru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Here, analytes were directly infused in the system individually at a concentration of 2 mg/L. Scan spectra were acquired in both positive and negative modes using MeOH, 0.1% formic acid in MeOH, and 0.2% ammonium formate in MeOH as infusion solvents based on the conditions previously reported in the literature. , Results indicated that positive mode provided better ionization for both ion sources since no signal was found for most of the analytes under negative mode (data not shown). Based on that, subsequent single ion monitoring (SIM), product ion (PI), and MRM studies were carried out with the aim to obtain MS/MS data of all target analytes in positive mode using both ESI and APCI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, analytes were directly infused in the system individually at a concentration of 2 mg/L. Scan spectra were acquired in both positive and negative modes using MeOH, 0.1% formic acid in MeOH, and 0.2% ammonium formate in MeOH as infusion solvents based on the conditions previously reported in the literature. , Results indicated that positive mode provided better ionization for both ion sources since no signal was found for most of the analytes under negative mode (data not shown). Based on that, subsequent single ion monitoring (SIM), product ion (PI), and MRM studies were carried out with the aim to obtain MS/MS data of all target analytes in positive mode using both ESI and APCI.…”
Section: Resultsmentioning
confidence: 99%
“…In the past years, targeted analysis of these compounds have been done usually by liquid chromatography (LC) combined with conventional detectors and/or mass spectrometry (MS) . All these methods have been focused on the determination of D 3 or hydroxylated metabolites. However, the analysis of ester forms has not been carried out so far in any type of sample, as described in a recent review article . The advantages of supercritical fluid chromatography (SFC) in terms of selectivity, comprehensiveness, and analysis speed together with its compatibility with a large range of different detectors have identified this technique as a promising alternative to LC .…”
mentioning
confidence: 99%